Targeted Next Generation Sequencing Revealed a Novel Homozygous Loss-of-Function Mutation in ILDR1 Gene Causes Autosomal Recessive Nonsyndromic Sensorineural Hearing Loss in a Chinese Family - An, Jinxia; Yang, Jie; Wang, Yan; Wang, Yanxia; Xu, Baicheng; Xie, Guangmei; Chai, Sanming; Liu, Xiaoling; Xu, Sijuan; Wen, Xiaoxiao; He, Qing; Liu, Huijun; et al. (Frontiers in Genetics, 2019)
Hereditary hearing impairment is one of the major and common birth defects in Chinese population. Non-syndromic sensorineural hearing loss (NSHL) is the most common types of hereditary hearing impairment. Genotypically and phenotypically NSHL is extremely heterogenous and follow either autosomal dominant, or autosomal recessive or X-linked mode of inheritance. Presently, 127 genes have been identified to be associated with both syndromic and non-syndromic sensorineural hearing loss. Here, we studied a Chinese family with moderate and profound hearing impairment. The proband is a 30-year old Chinese man. The proband was born with normal hearing and at the age of 5-years,the proband was first noticed with hearing impairment. Gradually and progressively the proband was presented with loss of hearing in his both right and left ears at the age of 30 years. The clinical symptoms, age of onset or progression to loss of hearing was similar in both the proband and his younger brother. The proband’s parents are phenotypically normal and non-consanguineous. Clinical diagnosis of the proband and his younger brother has been done by classical pure tone audiogram (PTA). Computed Tomography (CT) found no abnormality in bilateral external ear, middle ear and inner ear. Targeted next generation sequencing was performed with a panel of 127 genes reported to be associated with hereditary hearing impairment. A novel homozygous single nucleotide deletion (c.427delT) in exon 4 of ILDR1 gene has been identified in proband and in his younger brother. Sanger sequencing confirmed that proband’s father and mother are carrying this mutation in a heterozygous manner. This mutation has not been identified in 100 normal healthy control individuals. This mutation (c.427delT) causes frameshift (p.Tyr143Ilefs*19) which leads to the formation of a truncated ILDR1 protein of 162 amino acids instead of the wild type ILDR1 protein of 546 amino acids. ILDR1 associated hereditary hearing impairment is very rare and this is the first report of identifying a loss-of-function mutation in ILDR1 gene associated with hereditary hearing impairment in Chinese population. Our present study also emphasized the significance of rapid, accurate and cost-effective screening for the patient with hereditary hearing impairment by targeted next generation sequencing.